2002
DOI: 10.1046/j.1462-2920.2002.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of bacterial methyl halide degradation: biochemistry, genetics and molecular ecology

Abstract: Methyl halide-degrading bacteria are a diverse group of organisms that are found in both terrestrial and marine environments. They potentially play an important role in mitigating ozone depletion resulting from methyl chloride and methyl bromide emissions. The first step in the pathway(s) of methyl halide degradation involves a methyltransferase and, recently, the presence of this pathway has been studied in a number of bacteria. This paper reviews the biochemistry and genetics of methyl halide utilization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…Methyl halides are known to be produced in seawater by marine microorganisms (32)(33)(34)(35). Some methyl halides are known to be chemically removed from seawater by nucleophilic attack (36), hydrolysis (37), and bacteria (38)(39)(40). The observed decrease in CH 3 I was negatively correlated with CO 2 uptake and O 2 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl halides are known to be produced in seawater by marine microorganisms (32)(33)(34)(35). Some methyl halides are known to be chemically removed from seawater by nucleophilic attack (36), hydrolysis (37), and bacteria (38)(39)(40). The observed decrease in CH 3 I was negatively correlated with CO 2 uptake and O 2 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of C 1 compounds are consumed by methylotrophs in the environment, including methane, methanol, methylated amines, methylated glycines, halomethanes, and methylated sulfur species (1,21,24,31,44). Traditional microbial techniques such as enrichment and isolation on defined culture media have revealed that methylotrophic bacteria occur in a variety of environments, such as freshwater, marine, and terrestrial habitats, including habitats characterized by extreme conditions of temperature, salinity, or pH (8,26,44).…”
mentioning
confidence: 99%
“…As many methylotrophic bacteria are difficult to isolate, cultivation-independent molecular tools have been developed to characterize natural methylotrophic populations. These tools included oligonucleotide probes and PCR primer sets targeting genes conserved among methylotrophic bacteria, such as 16S RNA genes, or genes encoding specific methylotrophic enzymes, such as particulate and soluble methane monooxygenases, methanol dehydrogenase, corrinoid-linked methyltransferase, or methanesulfonic acid monooxygenase (3,15,21,30,31). However, none of these probes or primers aimed at detection of C 1 -oxidizing populations in a broader sense, encompassing their actual diversity.…”
mentioning
confidence: 99%
“…strain IMB-1 (41) were shown to be able to oxidize tropospheric concentrations of CH 3 Br (12 pptv), indicating that these and other methyl halide utilizers are responsible for the biological oxidation of tropospheric CH 3 Br and possibly CH 3 Cl in various terrestrial and marine environments (15). This also indicated that ambient concentrations of CH 3 Br and possibly CH 3 Cl were adequate for the induction of methyl halide utilization pathway(s).All four CH 3 Cl-utilizing soil isolates were found to possess the gene cmuA along with other CH 3 Cl-specific genes within their cmu (chloromethane utilization) gene clusters (6,31,32,50,54). The cmuA gene encodes methyltransferase I (CmuA), which catalyzes the initial dehalogenation step of the CH 3 Cl degradation pathway (Fig.…”
mentioning
confidence: 87%
“…All four CH 3 Cl-utilizing soil isolates were found to possess the gene cmuA along with other CH 3 Cl-specific genes within their cmu (chloromethane utilization) gene clusters (6,31,32,50,54). The cmuA gene encodes methyltransferase I (CmuA), which catalyzes the initial dehalogenation step of the CH 3 Cl degradation pathway (Fig.…”
mentioning
confidence: 99%